Studi Kasus Perawatan Luka Pada Pasien Diabetic Foot Ulcer Menggunakan Madu - Dwi Yogo Budi Prabowo; Risdiyanto Risdiyanto (JURNAL NERS LENTERA, 2023)
Patients with diabetes mellitus have complications. One complication experienced by the patient was a diabetic food ulcer. One of the preventions that can be done to overcome amputation is to improve wound healing in patients with complications of diabetic food ulcers. Treatment of dressings in healing diabetic food ulcers can be done by using herbal remedies such as honey. This research is a case study of the application of honey in the treatment of DFU wounds. Wound care using a TIME approach (Tissue Management, Infection Control, Moisture Balance and Edge of Wound. The results in this study an increase in tissue integrity after treatment for 3 weeks with an intensity of 3 times a week using honey.